2020
DOI: 10.18632/aging.103783
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles during postnatal development of the liver and pancreas in giant pandas

Abstract: Giant pandas are unique Carnivora with a strict bamboo diet. To investigate the molecular mechanism of giant panda nutrient metabolism from newborn to adult, the gene expression profiles of giant panda liver and pancreas tissues collected from three important feeding stages were investigated using RNA-seq. We found a total of 3,211 hepatic and 3,343 pancreatic differentially expressed genes (DEGs) from three comparisons between suckling and no feeding, adult and no feeding, and adult and suckling groups. Few d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…These tissue samples were immediately stored in a liquid nitrogen jar for RNA sequencing. Researches of giant panda also sample from accidental death individual (Peng et al 2018;Ma et al 2020). However, it is worth to note that the gene expression profiles of these samples may not totally reflect those from healthy GSMs.…”
Section: Sample Collection and Ethical Statementmentioning
confidence: 99%
“…These tissue samples were immediately stored in a liquid nitrogen jar for RNA sequencing. Researches of giant panda also sample from accidental death individual (Peng et al 2018;Ma et al 2020). However, it is worth to note that the gene expression profiles of these samples may not totally reflect those from healthy GSMs.…”
Section: Sample Collection and Ethical Statementmentioning
confidence: 99%
“…The energy-rich nutrient carbohydrate is a valuable calorie resource derived from low-fat and low-protein bamboo for adult red pandas and giant pandas, meeting their daily energy needs [ 64 , 65 , 66 ]. A previous study has demonstrated that high expression levels of genes related to carbohydrate metabolism in the liver of adult giant pandas enable them to effectively utilize carbohydrates from bamboo [ 9 ]. SLC5A4 can activate glucose sodium transporter activity and proton transmembrane transporter activity, thereby participating in carbohydrate utilization [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mammals undergo a dietary shift from birth to adulthood: they consume breast milk during the suckling period, while their dietary habits become diverse in adulthood, including carnivorous, omnivorous, and herbivorous diets. In order to meet nutrient utilization and energy needs for mammals at different stages of growth and development, the functions of digestive organs and expression levels of genes related to digestion and metabolism must adaptively change [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…genetic diversity despite their identical appearance (Li et al 2010;Zhao et al 2013;He et al 2020). However, due to the rarity of samples from this species, most experiments are limited to samples collected from dead bodies or the analysis of metabolites in specimens such as blood, urine, and feces to study the adaptability and genetic diversity of giant pandas (Li et al 2020;Ma et al 2020;Wu et al 2020). Because is difficult to collect tissue samples from live pandas, the hair color formation mechanism during the development of giant pandas is poorly understood.…”
Section: Introductionmentioning
confidence: 99%